The Effect of Intellectual Capital and Good Corporate Governance on Firm Value with Financial Performance as an Intervening Variable: Pengaruh Modal Intelektual dan Tata Kelola Perusahaan yang Baik Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Intervening - Septiawan, Fahrizal; Hermawan, Sigit (Indonesian Journal of Innovation Studies, 2022)
This study aims to determine the effect of intellectual capital and good corporate governance on firm value with financial performance as an intervening variable in High-IC Intensive companies listed on Indonesia Stock Exchange (IDX) in 2016-2019. The population in this study are Construction companies listed on the Indonesia Stock Exchange in 2016-2019. The sampling technique used in this research is purposive sapling. The analytical technique used in the research is Partial Least Square (PLS). The result of this study indicate that intellectual capital has no effect on financial performance. Good corporate governance has no effect on financial performance. Intellectual capital affects the value of the firm value. Good corporate Governance affects the value of the firm value. Fienancial performance has no effect on firm value. Financial performance is not able to mediatethe relationship between intellectual capital and firm value. Financial performance is not able to mediatethe relationship between good corporate governance and firm value.